(untitled) (Communications in Mathematical Research, 2020)
In this paper, we study one parameter deformation of full symmetric Toda hierarchy. This deformation is induced by Hom-Lie algebras, or is the applications of Hom-Lie algebras. We mainly consider three kinds of deformations, and give solutions to deformations respectively under some conditions.